Protective Embolization of the Gastroduodenal Artery with a One-HydroCoil Technique in Radioembolization Procedures - López-Benitez, Rubén; Hallscheidt, Peter; Kratochwil, Clemens; Ernst, Claudia; Kara, L.; Rusch, O.; Vock, P.; Kettenbach, J. (CardioVascular and interventional radiology, 2013)
Protective occlusion of the gastroduodenal artery (GDA) is required to avoid severe adverse effects and complications in radioembolization procedures. Because of the expandable features of HydroCoils, our goal was to occlude the GDA with only one HydroCoil to provide particle reflux protection.